Les collèges de proximités en Côte d’Ivoire sont-ils outillés à offrir un enseignement de qualité ? Étude de cas dans les collèges de Bourebo, Ayaou-Sokpa et Tienkoikro (International Journal of Scientific Research and Management (IJSRM), 2021)
In its logic of educating all children of school age and improving the school success rate, the Ivorian government continues to deploy strategies. As part of its strategies, mention should be made of the construction of colleges in some villages in order to bring learners closer to their parents. Do these new colleges have the necessary resources to offer quality education? This is the concern of this research which took place in the departments of Koun-Fao, Sakassou and Béoumi. This is a qualitative study. While the creation of local colleges has resolved the issue of bringing learners closer to their parents, the resources available to these establishments do not allow them to face the challenges of quality education.